Determinats and Impacts of Foreign Direct Investment in South Africa - Kassim, Leila Hashim (2008)
This paper examines the determinants and impacts of foreign direct investment in South Africa for the period 1970-2006. Recognising that FDI can contribute to economic growth and development of most countries, South Africa is constantly working to attract FDI and hence its demand has become highly competitive. South Africa has made considerable efforts over the past decade to improve their investment climate. They have liberalized their investment regulations and have offered incentives to foreign investors. This study therefore aims to determine the main determinants and impacts of FDI in South Africa. The study employs the use of the Eviews 6.0 software to carry out empirical tests of the unit root tests, cointegration analysis test and the granger causality test. All these tests would be used to achieve the set objectives of this study. The empirical results of this study reveal that the determinants of FDI in South Africa are human capital development and infrastructure, while the impacts of FDI in the country are increase in economic growth and export. This result agrees with several other empirical studies that have examined the determinants and impacts of foreign direct investment in other countries.